Effects of Eurycoma Longifolia Extract on the Isolated Rat Heart - RH, Mokhtar; N, Abdullah; A, Ayob (IIUM Medical Journal Malaysia, 2014)
Introduction: Eurycoma longifolia (E. longifolia) which is better known locally as Tongkat Ali is an indigenous plant in Malaysia. It belongs to the family of Simaroubaceae and is popular as a traditional medicine for its aphrodisiac properties. Throughout the years, several studies have been conducted to prove its effect on aphrodisiac action, antimalarial, antibacterial and anxiolytic properties but its effect to the cardiovascular system had not been fully explored. This study was aimed to demonstrate the changes that take place in the isolated heart following the injection of the extract. Methods: Three parameters that were measured included the coronary perfusion pressure (CPP), the left ventricular developed pressure (LVDP) and the heart rate (HR). Eighteen isolated rat hearts were used and were divided equally into three groups. The first group was to observe the effect of Isoprenaline, a β agonist while the second group was to see the effect of sodium nitroprusside (SNP), a nitric oxide (NO) donor. The dose which gave the maximum effect for these two positive controls was used to compare with the effect of E. longifolia water extract in the third group of rats. Isolated heart was mounted using the Langendorff apparatus and perfused with modified Krebs-Henseleit buffer. Doses of controls and the extract were instilled through an injection port, and the effect of each dose was monitored. Results: E. longifolia extract was found to reduce the CPP in normotensive rat at two of the highest doses. A dose of 1.0 mg of the extract reduced the CPP significantly from 34.52 ± 4.99 mmHg of the baseline value to 31.99 ± 4.93 mmHg while the dose of 10.0 mg of the extract reduced the CPP significantly to 32.67 ± 3.89 mmHg. However, there were no significant changes of effect of the extract on the LVDP and HR as compared to control. Conclusion: These early findings suggest that E. longifolia extract may have vasodilatory property, which supports its traditional usage with minimum cardiovascular side effects.